Control of excitation transfer in coupled quantum dots by a nonresonant laser pulse. (August 2015) - Astapenko, V.A.; Golovinski, P.A.; Yakovets, A.V.
Abstract: We study theoretically fast transfer of excitons between pairs of coupled quantum dots driven by the optical Stark effect that is produced by a short nonresonant laser pulse. The Schrödinger equation, in which the relative position of energy levels of quantum dot subsystems is time-dependent, is solved numerically. Computer simulation demonstrates the mechanism of controlling the efficient excitation transfer by the action of a picosecond laser pulse with a flat-top intensity profile.